Cardiovascular benefits of sodium-glucose cotransporter 2 inhibitors in diabetic and nondiabetic patients - Boyang Xiang; Xiaoya Zhao; Xiang Zhou (Cardiovascular Diabetology, 2021)
Abstract Sodium-glucose cotransporter 2 inhibitors (SGLT2i) were developed as antidiabetic agents, but accumulating evidence has shown their beneficial effects on the cardiovascular system. Analyses of the EMPA-REG OUTCOME trial (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients) suggested that these benefits are independent of glycemic control. Several large-scale outcome trials of SGLT2i also showed cardiovascular benefits in nondiabetic patients, strengthening this perspective. Extensive animal and clinical studies have likewise shown that mechanisms other than the antihyperglycemic effect underlie the cardiovascular benefits. Recent clinical guidelines recommend the use of SGLT2i in patients with type 2 diabetes mellitus and cardiovascular diseases because of the proven cardiovascular protective effects. Since the cardiovascular benefits are independent of glycemic control, the therapeutic spectrum of SGLT2i will likely be extended to nondiabetic patients.